2013
DOI: 10.4103/0970-1591.117279
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three different techniques of extraction in laparoscopic donor nephrectomy

Abstract: Aim:We compare the outcome of three different methods of graft extraction after a laparoscopic donor nephrectomy.Materials and Methods:After a conventional five port laparoscopic donor nephrectomy, specimen was extracted through one of three approaches: 1. Iliac fossa (IF) incision and hand extraction, 2. Midline (MD) periumbilical with a lower polar fat stitch incorporating gonadal vein for traction while retrieval, and 3. Pfannensteil (PF) with Gel port extraction. Estimated blood loss, operating time, warm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 12 publications
(18 reference statements)
0
18
0
Order By: Relevance
“…The quality of included studies was generally low with randomisation occurring in only one study [ 8 ]. In the retrospective studies, there was no clear protocol for treatment allocation; this tended to be performed at the discretion of the surgeon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of included studies was generally low with randomisation occurring in only one study [ 8 ]. In the retrospective studies, there was no clear protocol for treatment allocation; this tended to be performed at the discretion of the surgeon.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies, performing donor nephrecromy (DN) [ 8 , 9 ], found the procedure to be statistically longer in the PFN group ((two studies, 396 participants): 95% MD -10.21, 95% CI from -19.46 to -0.96, p = 0.03, I 2 = 0%). A limitation to this dataset is that Gupta [ 9 ] did not provide variance data and as such, the standard error was extrapolated from the provided p-value (0.15) to generate a t-value (SD = t/SE).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas with a Pfannenstiel incision, the rectus abdominis muscles are retracted once the anterior rectus sheath is incised, thus requiring less time to approximate the muscles and the sheath. Gupta et al [10] and Adiyat et al [3] in their respective studies did not find a significant difference in mean operating time. Binsaleh et al [11] compared the Pfannenstiel incision with an extended port-site incision in laparoscopic radical nephrectomy and found no statistically significant difference in operative time.…”
Section: Discussionmentioning
confidence: 86%
“…This finding concurs with the finding in the Gupta et al [10] study (3 vs 3.5 min, P = 0.18). However, in the Adiyat et al [3] study, the WIT was significantly less in the Pfannenstiel-incision arm as compared to the iliac fossa-incision and midline-incision arms [mean (SD) 175 (59) vs 241 (62) vs 206 (49) s; P < 0.001]. In our present study, we additionally recorded the retrieval time, which was defined as the time from placement of first Hem-o-lok® clips (Weck Closure Systems, Research Triangle Park, NC, USA) on the renal artery until the time the kidney was extracted and placed on the ice slush.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation